2021
DOI: 10.3389/fneur.2021.591586
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and Clinical Value of 7T MRI for Evaluating 3T-Visible Lesions in Pharmacoresistant Focal Epilepsies

Abstract: Objective: The recent FDA approval of the first 7T MRI scanner for clinical diagnostic use in October 2017 will likely increase the utilization of 7T for epilepsy presurgical evaluation. This study aims at accessing the radiological and clinical value of 7T in patients with pharmacoresistant focal epilepsy and 3T-visible lesions.Methods: Patients with pharmacoresistant focal epilepsy were included if they had a lesion on pre-operative standard-of-care 3T MRI and also a 7T research MRI. An epilepsy protocol was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…While the anterior lesion was classified as FCD IIb, no FCD was diagnosed for the posterior lesion. As the patient did not get seizure-free the posterior lesionectony was extended and histology now revealed a FCD IIa Tesla MP2RAGE images have been with 3 Tesla MPRAGE images [37,38]. This comparison is biased as postprocessing using MP2RAGE images already displays FCD with larger volumes and higher z scores [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the anterior lesion was classified as FCD IIb, no FCD was diagnosed for the posterior lesion. As the patient did not get seizure-free the posterior lesionectony was extended and histology now revealed a FCD IIa Tesla MP2RAGE images have been with 3 Tesla MPRAGE images [37,38]. This comparison is biased as postprocessing using MP2RAGE images already displays FCD with larger volumes and higher z scores [34].…”
Section: Discussionmentioning
confidence: 99%
“…There is strong agreement that the visibility on MRI depends on the FCD type: FCD type II are visible on MRI provided adequate image quality on 3 Tesla machines and postprocessing is achieved. It has been reported that 7 Tesla is superior to 3 Tesla; however, post-processed 7 Tesla MP2RAGE images have been compared with 3 Tesla MPRAGE images [ 37 , 38 ]. This comparison is biased as postprocessing using MP2RAGE images already displays FCD with larger volumes and higher z scores [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI-negative is a misnomer that comprises patients without an MRI lesion or with a subtle MRI lesion but being overlooked ( 8 ). Although high-field imaging and postprocessing techniques have dramatically improved the detection rate of FCD, there are still limitations in the artifacts ( 22 ), the high false positive rate outcome ( 23 ), and clinical application promotion. Due to the preferential occurrence of dysmorphic neurons in deep cortical layers ( 24 , 25 ), MRI abnormalities are mostly displayed close to the gray matter–white matter interface.…”
Section: Discussionmentioning
confidence: 99%
“…A further systematic review gave comparable results [4]. In individuals with lesions seen at 3T, 7T imaging was associated with increased conspicuity and definition of boundaries but with increased artefacts, particularly in the temporal lobes [5], and there was benefit from postacquisition morphometric analysis in individuals with unremarkable scans at 3T [6].…”
Section: Mrimentioning
confidence: 94%